Terazosin‐induced alterations in catalase expression and lipid peroxidation in the rat seminal vesicles. (26th June 2012) - Mitropoulos, D.; Patris, E.; Deliconstantinos, G.; Kyroudi‐Voulgari, A.; Anastasiou, I.; Perea, D.
Summary Previous studies have shown that alpha1‐adrenergic receptor antagonists may alter seminal vesicle contractility and impair fertility in male rats. This study was designed to investigate the effects of terazosin on the catalase expression in the seminal vesicles and the lipid peroxidation of the seminal fluid in normal adult rats. Wistar rats were treated with terazosin (1.2 mg kg−1 body weight, given orally every second day) for 120 days. Catalase expression was assessed immunohistochemically in tissue sections of the seminal vesicles, and lipid peroxidation was estimated by measuring the malondialdehyde (MDA) levels in the seminal vesicles' fluid. The seminal vesicles in terazosin‐treated rats were particularly distended in comparison with those of controls, and their secreting epithelium was suppressed. Cytoplasmic catalase expression in the secreting epithelial cells (% of cells) was increased in terazosin‐treated specimens in comparison with controls (76.1 ± 17.1 versus 51.3 ± 25.1, P = 0.005). MDA levels (μm) were also higher in samples from treated subjects in comparison with controls (2.67 ± 1.19 versus 1.39 ± 0.19, P = 0.01). Although the direct effect of terazosin treatment on the seminal vesicles is that of impaired contractility, an indirect effect is that on fertility by increasing lipid peroxidation in the seminal fluid and/or through degrading of hydrogen peroxide that is essential for sperm capacitation.